Analisis Perbandingan Ekuitas Merek Kedai Kopi Janji Jiwa dengan Kedai Kopi Kenangan di Kota Malang - Fera Nur Amalia; Bambang Yudi Ariadi; Dyah Erni Widyastuti (AGRIMOR, 2022)
Today's business competition is limited to the functional attributes of the product and has been associated with the brand. This study aims to determine whether there is a difference in brand equity and its elements between the Promise Jiwa Coffee Shop and Kenangan Coffee Shop in Malang City. The design of this study used a survey method with sampling using a non-probability sampling technique. The research data used primary data obtained from interviews and the distribution of questionnaires. Respondents from this study were consumers of the two consumers, who had visited at least twice. The number of respondents was 160 people, 80 respondents from the Janji Jiwa coffee shop and 80 respondents from the Kenangan coffee shop. Data analysis used descriptive statistics of percentages and independent t-test differences. The results of the study based on descriptive analysis of the percentages for the variables of brand awareness, brand association, perceived quality, and brand loyalty from the two shops have positive values. Respondents' answers were dominated by answers that strongly agree and agree. Based on the results of the independent t-test analysis, it shows that the elements of brand equity and brand equity of the two shops in Malang City do not have a significant difference.